Peristiwa G 30 S sebagai Isu Kontroversial pada Mata Pelajaran Sejarah di SMA Kota Bima - Edy Suparjan (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2016)
This study aimed to describe the process of teaching history with event materials G 30 S. This study implemented for three months housed in SMAN 2 and SMAN 4 Kota Bima. The method used is a qualitative method using analytical descriptive. Collecting data in this study using the method of observation, interviews and documentation. Sources of key data used in this research: key informant and the informant is vice principal core curriculum is a history teacher and student. Data were analyzed using analysis of Huberman Milles ie, data reduction, data presentation and then verify and pengambilam conclusions. The results showed that the learning G30S lasted less monotonous and attract students, the method used by the teacher has not varied, instructional media used was whiteboard reference books still use textbooks published by private simple. Besides infrastructure such as, Laptops, LCD, and VCD do not support learning activities in the classroom. The issue of revival of the PKI and government apology to the victim less of an effect on learning about the material G 30 S in school, especially in the city of Bima. This is because the curriculum is implemented using the curriculum in 2006.